COMMUNICATIVE MEANS OF NETWORK POSITIONING OF CULTURAL ADVANCEMENT OF THE REGION - Prystai, H. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2019)
The article examines the development of arts and cultural information by the cultural institutions; the semantic components of cultural content are analyzed on the basis of the activity of libraries in Ukraine.